2007
DOI: 10.1007/s10553-007-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective friction modifiers from nano-sized materials

Abstract: Synthesis and the tribological properties of oil-soluble friction modifiers made from surface-modified (lyophilized) nanoparticles of molybdenum trisulfide (nano-MoS 3 ) are described. The synergistic effect of nano-MoS 3 and zinc dialkyldithiophosphate (ZnDDP) is demonstrated. Addition of the latter is effective at high temperatures and low concentrations.The increase in the price of crude and petroleum products has made it necessary to conserve sources of energy. One of the fundamental methods of reducing fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…So, surface modification was proposed to improve the solubility in nonpolar hydrocarbon oils. The synergistic effect of surface-modified nanoparticles of molybdenum trisulfide (nano-MoS 3 ) and ZDDP was demonstrated [21].…”
Section: Overview Of Organomolybdenum Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…So, surface modification was proposed to improve the solubility in nonpolar hydrocarbon oils. The synergistic effect of surface-modified nanoparticles of molybdenum trisulfide (nano-MoS 3 ) and ZDDP was demonstrated [21].…”
Section: Overview Of Organomolybdenum Compoundsmentioning
confidence: 99%
“…In the last few years, it has been proposed in many patents and articles that the derivatives of alcohol (7,8), ether (9), ester (19,20), mercaptocarboxylate (21,22), thioester (23) and carboxylate (24,25) are useful friction modifiers in lubricants ( Fig. 4) [62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Carboxylates and Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, MoS 3 can be synthesized by liquid-phase reaction in ambient environment [14], which is suitable for the synthesis of the CDC-based composites. On the other hand, MoS 3 possesses good lubricating behaviors [15][16][17]. Lince et al [18] demonstrated that MoS 3 exhibited excellent lubricating ability, which is identical to the well-known MoS 2 solid lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nano-sized lubricant additives as friction modifier is beneficial because it might reduce the use of phosphorus containing additives. Phosphorus containing additives are not environment friendly [12]. Additionally, NPs can easily enter fine asperities where micro-sized particles cannot reach.…”
Section: Introductionmentioning
confidence: 99%